2018
DOI: 10.2147/ott.s154517
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA 302b-3p/302c-3p/302d-3p inhibits epithelial–mesenchymal transition and promotes apoptosis in human endometrial carcinoma cells

Abstract: BackgroundStudies have shown that the microRNA miR-302 can affect the proliferation, migration and cell cycle progression of endometrial carcinoma (EC). miR-302 clusters have been shown to play an important role in the proliferation and differentiation of cancer cells and in their tumorigenicity.Subjects and methodsIn this study, we detected the expression of genes through quantitative reverse transcription polymerase chain reaction (qRT-PCR). We detected the expression of proteins through Western blot. The An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
(20 reference statements)
0
19
0
Order By: Relevance
“…It has been reported that miR-302s inhibits CDK4 and CCND1 expression and regulates cell cycle [15,16]. Moreover, the miR-302s decreased cancer cell proliferation by down-regulating the SDC1, SOX1 and SHH [17]. Thus, miR-302s showed tumor suppressive activity in a number of solid tumors.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that miR-302s inhibits CDK4 and CCND1 expression and regulates cell cycle [15,16]. Moreover, the miR-302s decreased cancer cell proliferation by down-regulating the SDC1, SOX1 and SHH [17]. Thus, miR-302s showed tumor suppressive activity in a number of solid tumors.…”
Section: Discussionmentioning
confidence: 94%
“…One study of malignant pleural mesothelioma indicated that miR‐302b can inhibit tumor cell tumorsphere growth by targeting Mcl‐1 to inhibit proliferation and induce apoptosis . Additionally, in HECCs, miR‐302b/c/d was confirmed to promote apoptosis by downregulating zinc‐finger E‐box binding homeobox 1 and Bcl‐2 and upregulating BAX …”
Section: Functions and Mechanisms Of Mir‐302 Cluster In Tumor Developmentioning
confidence: 94%
“…Wound healing assay were performed according our previously described [29]. Cells were observed by microscopy and photographed (0 h and 24 h cell scratches).…”
Section: Wound Healing Assaymentioning
confidence: 99%